Numerical Simulations of Dynamic Performances of the U-tube Ground Source Heat Pumps System - Ji Feng; Su Hua; Liu Sainan; Liao Gaohui (Zhileng xuebao)
Simulations of the dynamic performance of a ground heat pump system are important to the system design. Based on a one-dimensional numerical transient heat transfer model, a coupling simulation algorithm was developed for the U-tube ground source heat pump system. Given hourly building loads, ground properties and heat pump performance data, this method can compute the ground temperature, the water temperature and energy consumptions, which are the basis of system assessment. Comparisons between this numerical method and an analytical method show that this numerical method is accurate and fast. A one-year-period case study is hourly carried out and recommendations are given regarding to quantity and distance of boreholes based on simulated results.